Graft dysfunction immediately after reperfusion predicts short-term outcomes in living-donor lobar lung transplantation but not in cadaveric lung transplantation - Mizota, Toshiyuki (Interact Cardiovasc Thorac Surg, 2016)
OBJECTIVES: Primary graft dysfunction (PGD) is a major cause of early morbidity and mortality after cadaveric lung transplantation (CLT). This study examined the incidence, time course and predictive value of PGD after living-donor lobar lung transplantation (LDLLT). METHODS: We retrospectively investigated 75 patients (42 with LDLLT and 33 with CLT) who underwent lung transplantation from January 2008 to December 2013. Patients were assigned PGD grades at six time points, as defined by the International Society for Heart and Lung Transplantation: immediately after final reperfusion, upon arrival at the intensive care unit (ICU), and 12, 24, 48 and 72 h after ICU admission. RESULTS: The incidence of severe (Grade 3) PGD at 48 or 72 h after ICU admission was similar for LDLLT and CLT patients (16.7 vs 12.1%; P = 0.581). The majority of the LDLLT patients having severe PGD first developed PGD immediately after reperfusion, whereas more than half of the CLT patients first developed severe PGD upon ICU arrival or later. In LDLLT patients, severe PGD immediately after reperfusion was significantly associated with fewer ventilator-free days during the first 28 postoperative days [median (interquartile range) of 0 (0–10) vs 21 (13–25) days, P = 0.001], prolonged postoperative ICU stay [median (interquartile range) of 20 (16–27) vs 12 (8–14) days, P = 0.005] and increased hospital mortality (27.3 vs 3.2%, P = 0.02). Severe PGD immediately after reperfusion was not associated with ventilator-free days during the first 28 postoperative days, time to discharge from ICU or hospital, or hospital mortality in CLT patients. CONCLUSIONS: Postoperative incidence of severe PGD was not significantly different between LDLLT and CLT patients. In LDLLT patients, the onset of severe PGD tended to be earlier than that in CLT patients. Severe PGD immediately after reperfusion was a significant predictor of postoperative morbidity and mortality in LDLLT patients but not in CLT patients.